URGENSI PENDIDIKAN NILAI UNTUK MEWUJUDKAN KARAKTER BANGSA DI SEKOLAH DASAR DALAM PEMBELAJARAN IPAS - Rustini, Tin; Gunawan, Aliya Putri; Laeni, Mega (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The progress of a nation is strongly influenced by education which serves as the main key in shaping the nation's civilization. Value education is an important element to be taught in elementary schools, especially in integrating the five basic values of educative, practical, theoretical, philosophical, and divine (religious) values into IPAS (Natural and Social Sciences) learning. This study aims to investigate and analyze the urgency of value education through IPAS learning in elementary schools. The research method used is qualitative with a literature study approach that analyzes various relevant literature studies. The results showed that value education in IPAS learning helps students develop intellectual abilities, skills, and moral attitudes that support the formation of strong character. This positive response cannot be separated from the implications of using fun learning strategies and utilizing technology as an interactive learning media. In addition, the role of teachers, parents, and the community is also very important for the realization of children's virtuous character. Thus, through the integration of educational, practical, theoretical, philosophical, and religious values into IPAS learning, it is expected to create a generation that is not only academically intelligent but also has a positive attitude and good ethics to face future challenges.